Effect of shading during the establishment of Megathyrsus maximus cv Mombaza in association with Arachis pintoi Krapov in Ecuador (Bioagro, 2023)
An investigation was carried out with the objective of evaluating the effect of shading during the establishment of the grass Megathyrsus maximus cv. Mombaza in association with Arachis pintoi Krapov, in Santo Domingo de los Tsáchilas, Ecuador. A complete randomized block design, with split plot arrangement and three replications, was used, where three factors under study were evaluated: Shade 40 %, 24 %, 10 % and no shade, monoculture from Mombaza and in association with Arachis (70 and 30 %, respectively) and seasons of the year (rainy and dry).  The variables evaluated were: dry matter yield, leaf-stem ratio and crude protein content.  The results showed that the establishment condition (monoculture or associated) did not affect (P>0.05) the performance of the pasture. During the rainy season, the highest (P≤0.05) dry matter yield was recorded with 4.39 Mg∙ha-1.cut-1 compared to the dry season (3.77 Mg∙ha-1.cut-1). There was a significant reduction (P≤0.05) in yield at a shade level of 40 %. The best values ​​of the leaf:stem ratio were observed with a shade level of 24 % in the rainy season with 2.87. The best protein level was observed in the dry season (11.7 %), in association with forage peanuts (11.9 %) and an average of 12.27 % under shade.  The cultivar Mombaza can be established in silvopastoral systems with medium levels of shade that do not affect yield but improve quality.
Keywords: Pinto peanut; silvopastoral system; yield